RONGGENG DI NAGARI UJUNG GADING KECAMATAN LEMBAH MALINTANG KABUPATEN PASAMAN - Mailizar Mailizar; Erfan Erfan; Yos Sudarman (SENDRATASIK UNP, 2018)
Abstract This article aims to describe the Ronggeng in Nagari Ujung Gading Kecamatan Lembah Malintang Kabupaten Pasaman. This type of research is qualitative research with descriptive analysis approach. With this type of approach and research, key informant researcher himself, and another informant has a very important role in the collection of data and information for the study. Engineering data collection studies namely librarianship, plus interviews and observations and photo shoots. Data processing with identify, classify, analyse, describe the return of primary and secondary research data collected. Research results can be explained that such ronggend West Pasaman ronggeng art that is on the tip of ivory, Nagari is an art that is considered original ronggeng by local mnasyarakat. Ronggeng is still performed in the various activities of the nagari (which pioneered the young) as well as in the activities of alek nagari with ceremonial purposes and societal. These are presented in the form of Ronggen dances accompanied by music and pantun. In his musical accompaniment, ronggeng using instruments violin, drums, tambourines, and bottles. Ronggeng is the traditional art at West Pasaman which needs to be passed down from generation to generation. Keywords: Ronggeng